Managing Curriculum-Based ESL Assessment through the SACSA Framework: Evidence from Written and Oral Learner Performance - Amalia Lakehu; Sri Ningsih (Bata Ilyas Educational Management Review, 2026)
This study assesses the written and oral performance of English as a Second Language (ESL) learners through the South Australian Curriculum Standards and Accountability (SACSA) framework. The assessment focuses on four language dimensions: Genre, Field, Tenor, and Mode. The data consist of one written personal recount produced by a primary-years student and one oral personal information report delivered by a middle-years student. This study uses a formative, performance-based assessment approach. Student evidence was matched with the descriptors of the SACSA ESL Scope and Scales to identify proficiency levels and instructional needs. The findings show that both students performed satisfactorily at Scale 3. They demonstrated a basic understanding of the assigned genres and could communicate simple information. However, both students still showed limitations in content elaboration, grammatical accuracy, vocabulary range, evaluative language, sentence variation, and tense consistency. The results indicate that the SACSA framework can help teachers diagnose language development more precisely. ESL instruction should strengthen scaffolding, explicit genre teaching, contextual vocabulary development, and timely formative feedback to support gradual improvement in written and oral communication.